Effects of garden soil and organic substrates ratio on the growth of eggplant (Solanum melongena L.) plug transplants - Villanueva, Isagani P.; Valdez, Manolo T. (2010)
The study was conducted to determine the effects of garden soil and organic substrate ratios on the growth of eggplant plug transplants; and to determine the best ratio of garden soil and organic substrate for eggplant plug transplant production. The study consisted of three setups: Set-up A: garden soil (GS) and rice straw compost (RSC) mixture, Set up B: garden soil (GS) and carbonized rice hull (CRH) mixtures, and Set up C garden soil (GS) and biogas sludge (BS) mixtures. The experimental set-up was laid out in a simple Completely Randomized Design (CRD). The treatments were replicated three (3) times. Seedling height was significantly improved using pure (100%) rice straw compost (RSC) and mixtures of garden soil (GS) and 25% to 75% RSC. Mixture of 25%GS:75% BS markedly influenced the shoot fresh weight and the total leaf area of plug transplants five weeks after sowing. 50% GS:50%CRH produced plugs with high shoot fresh and dry weights, total leaf area, internode length, and seedling height.
Keywords: Eggplant growing; Eggplant